1988
DOI: 10.1002/etc.5620070308
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of brass powder‐contaminated soil by the earthworm, lumbricus terrestris

Abstract: Tests of the avoidance of brass powder (70% Cu, 30% Zn) contaminated soils by the earthworm Lumbricus terrestris at concentrations ranging from 0 to 200 μg/g were conducted. Avoidance was significant (p < 0.001) at brass concentrations as low as 38 μg/g. Avoidance was found to be a more sensitive indicator of the impact of brass powder on the worms than sublethal effects measured by weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…Growth can therefore be considered a sensitive parameter in determining the e!ects of copper oxychloride at these concentrations on E. fetida. The e!ects on the growth rate of the worms could have been a result of poor feeding due to the presence of copper oxychloride, since earthworms are able to detect and avoid copper (Ma, 1988;Wentsel and Guelta, 1988). Svendsen and Weeks (1997) observed inhibited feeding at a soil copper concentration of 320 mg 112 kg soil\, where there were also reductions in growth and survival.…”
Section: Discussionmentioning
confidence: 96%
“…Growth can therefore be considered a sensitive parameter in determining the e!ects of copper oxychloride at these concentrations on E. fetida. The e!ects on the growth rate of the worms could have been a result of poor feeding due to the presence of copper oxychloride, since earthworms are able to detect and avoid copper (Ma, 1988;Wentsel and Guelta, 1988). Svendsen and Weeks (1997) observed inhibited feeding at a soil copper concentration of 320 mg 112 kg soil\, where there were also reductions in growth and survival.…”
Section: Discussionmentioning
confidence: 96%
“…Wentsel and Guelta (1988) observed that L terrestris avoided soil containing brass (70% Cu, 30% Zn) at 35 mg/kg but not at 17 mg/kg. A voidance responses were also observed for E. fetida exposed to soil contaminated with KCl and ~Cl, but not when exposed to 2-chloro-acteamide (Yeardley et al 1996).…”
Section: Behavioral Responsesmentioning
confidence: 89%
“…Studying the transport of slug pellets to burrows, Bieri et al (1989) observed that L terrestris exhibited little transport of slug pellets containing methiocarb (a carbamate insecticide), but extensive transport of metaldehydecontaining pellets, the latter causing increased mortality. Few studies described a dose-response relationship between the behavioral effects and soil dose, but Wentsel and Guelta (1988) observed a decreasing number of worms in soils contaminated with increasing brass powder concentrations. The worms were able to choose a clean soil.…”
Section: Behavioral Responsesmentioning
confidence: 93%
“…Systematic study has yet to determine the sensory mechanisms by which earthworms discriminate and avoid soils with undesirable concentrations of toxic metals. However, their avoidance of various inorganic and organic contaminants is well-attested (Alvarenga et al 2008;HundRinke et al 2005;Sousa et al 2008;Wentsel and Guelta 1988;Yeardley et al 1996). While earthworms avoid soil with undesirable chemistry, they also demonstrate complex feeding preferences that includes discrimination between food and soil based on microbial colonization, mechanical and chemical properties of organic matter (Bonkowski et al 2000;Curry and Schmidt 2006;Doube et al 1997).…”
Section: Introductionmentioning
confidence: 95%
“…In turn, earthworm extinction caused by metal contamination has been linked to soil compaction and excessive litter buildup in (Eijsackers et al 2005;Rombke et al 2005;Van Zwieten et al 2004) both of which are detrimental to soil quality. Recent research indicates that earthworms actively avoid metalcontaminated soils at concentrations that are lower than those that cause direct toxicity (Alvarenga et al 2008;Langdon et al 2005;Wentsel and Guelta 1988). Rather than directly eliminating earthworms through impacts on their survival, growth and reproduction, contaminants may repel earthworms from an area and deter immigration even after the pollution activity has ceased (Eijsackers et al 2005;Klok et al 2007).…”
Section: Introductionmentioning
confidence: 98%